The Effectiveness of Logistic Regression Analysis in Classification of normal and mentally disabled children according to their performance on Part One of the Adaptive Behavior Scale (Journal of Hama University, 2020)
The research aims to identify the eeffectiveness of logistic regression analysis in Classification of normal and mentally disabled children according to their performance on Part One of AAMR adaptive behavior Scale. The research sample consisted of  normal childrennumbered 310, of whom 167 males and 143 females, and consisted of mentally retarded children numbered 122 children: 73 Males and 49 females.The research obtains the following results:1.      Adapt the logistic regression model to the fields of part one of the adaptive behavior scale.2.      There is Predictability of five fields of part one of the adaptive behavior scale (self-direction, number and time, socialization, independent functioning, vocational) in the classification of children search sample individuals.3.      The quality of conciliation model of logistic regression analysis in full, and the quality of the classification where the percentage of children who were classified As normal was (98.7%), and the percentage of children who were classified mentally retarded was (98.4%), While the percentage of the correct classification of the total sample was (98.6%).The importance of this research is to benefit from logistic regression analysis and its use in the service of research purposes in the field of education and psychology.